Bahasa Inggris - Nengsih, Nelda Novia; Fifi Yasmi; Dina Amaluis (Global Action and Education for Society, 2025)
This study aims to determine 1) the effect of learning habits on students' interest in learning, 2) the effect of learning discipline on students' interest in learning, 3) the effect of students' perceptions of teachers' teaching methods on students' interest in learning, 4) the effect of parental attention on students' interest in learning, 5) the effect of learning habits on academic achievement, 6) the effect of learning discipline on academic achievement, 7) the effect of students' perceptions of teachers' teaching methods on academic achievement, 8) the effect of parental attention on academic achievement, and 9) the effect of learning interest on academic achievement. The research was conducted in July 2025. This research is associative in nature. The population in this study consists of 104 eleventh-grade students at SMA Negeri 5 Padang, with a sample selected using proportional random sampling. The data analysis techniques used were descriptive analysis and path analysis, with the assistance of Eviews 13 and SPSS version 22.0. The research results showed that: 1) study habits did not significantly influence students' interest in learning, with a path coefficient value of -0.053 and a calculated t-value of 0.865 ≤ t-table 1.660, 2) Learning discipline significantly influences students' learning interest with a path coefficient of 0.399 and a calculated t-value of 5.277 ≥ t-table 1.660, 3) Students' perceptions of teachers' teaching methods influence students' learning interest with a path coefficient of 0.195 and a calculated t-value of 2.276 ≥ t-table 1.660, 4) There is an effect of parental attention on students' learning interest with a path coefficient value of 0.386 and a t-value of 5.007 ≥ t-table 1.660, 5) There is an effect of learning habits on learning achievement with a path coefficient value of 0.210 and a t-value of 2.626 ≥ t-table 1.660, 6) There is an influence of learning discipline on academic achievement with a path coefficient value of -0.013 and a t-value of -2.826 ≥ t-table 1.660, 7) There is an influence of students' perceptions of teachers' teaching methods on academic achievement with a path coefficient value of 0.408. This coefficient value is significant because the t-value is 3. 587 ≥ t table 1.660, 8) There is an effect of parental attention on academic achievement with a path coefficient value of 0.371. This coefficient value is significant because the t-value is 3.322 ≥ t table 1.660, 9) There is an effect of learning interest on academic achievement with a path coefficient value of -0.823. This coefficient value has a negative and significant effect because the t-calculated value is -6.326 ≥ t-table 1.660.